Spatial disinfection potential of slightly acidic electrolyzed water. - Midori Kurahashi (Public Library of Science (PLoS), 2021)
Slightly acidic electrolyzed water (SAEW) was developed by Japanese companies over 20 years ago. SAEW has the advantage of potent sterilizing action while being relatively safe. This study evaluated the potential application of SAEW in spatial disinfection. Prior to experiments involving spatial spraying, the ability of SAEW to remove seven type of microorganisms that cause food poisoning was studied in vitro. Results indicated that free chlorine in SAEW, even at a low concentration (30 mg/L), was able to remove Cladosporium cladosporioides, a typical airborne fungus that degrades food, and spores such as Bacillus subtilis, a hardy bacterium. In an experiment involving spatial spraying, 3.43 log10 CFU/100 L of Staphylococcus epidermidis was sprayed in a room-sized space; the same space was then sprayed with SAEW. The number of settling microbes was measured and the sterilizing ability of SAEW was assessed. Results indicated that the concentration of S. epidermidis in the space was completely removed after 20 minutes of SAEW spraying. The above findings indicate that SAEW may be used to remove airborne microorganisms via spatial spraying.